“Aplicación de medicamentos homeopáticos en plantas de cilantro (Coriandrum sativum L.) bajo cubierta protegida en el cantón Pujilí”. - Bravo Romero, Edison Joel (2023)
The current research work was carried out in the Pujilí Canton to determine the agronomic response of the coriander crop (Coriandrum sativum L.) taking into account the application of homeopathic medicines under protected cover. A randomized block design (DCBA) was used with a factorial arrangement of (2 x 3+1) where factor A represented the homeopathic medicines (1 and 2), and factor B represents the centesimal dilutions (1C, 2C, and 3C)., and a control, all of them with four repetitions. There was an evaluation of agronomic variables of importance in the coriander cultivation, such as plant height, number of branches, number of flowers, and dry and fresh weight of the plant, all of these values were taken every 15 days until 60 days old, as well as yield and concentration of flavonoids that were taken only at the end of the experiment (60 days). The most relevant results were at 60 days, as follows: the best height plant treatment (T6) with 35 cm, while in the other variables, the one that showed the greatest variables was T5, thus: number of branches 13.50, fresh plant weight 8.22g, dry plant weight 2.77g, number of flowers 11.23, a growth rate of 0.0453g/day and yield of 1409Kg/Ha and concerning flavonoids a quantity of 3.3g/kg DM. While in the economic analysis a profitability was represented in all the treatments being 17% the highest (homeopathic medicines 1), followed by 2 with 9%.